Ngepan Iban: A Cultural Expression of Identity, Values, and Heritage in the Iban Community of Sarawak - Noria, Tugang; Follysia Julan, Stap; Louis Ringah, Kanyan; Laura Pranti, Tutom; Alexander, Chelum; Greogory, Kiyai (2025)
This study aims to explore Ngepan Iban, the Iban's people's traditional attire in Sarawak, as it provides a cultural representation of the Iban, a symbol of their identity, values, and beliefs. Ngepan Iban is more than an attire, it is a cultural object which exists in ceremonial, spiritual, and community social ways. To study its history, symbolic meanings, and ritualistic functions: Ngepan Iban becomes a visualization or canon of cultural representation or a record of traditional knowledge and cultural memory. The research used qualitative research methodologies that included collecting data from interviews with cultural specialists, tribal elders, and practitioners of the traditional art plan of Ngepan Iban. The research makes an argument for Ngepan Iban is a pictorial embodiment of the community's aesthetic skill and its artistic achievements; and as an artefact used for the preservation of cultural knowledge, it can recreate a social identity and enrich social pride. It is hoped that the contributions made in this study can position Ngepan Iban as symbolically sustainable (long lasting) as an Iban cultural heritage, and add to the larger discussions about culture, preservation, and identity.